THE CONCEPT OF ECOSYSTEM SERVICES - Strode, Skaidrīte; Noviks, Gotfrīds (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2023)
The world’s natural capital is shrinking faster and faster. Loss of biodiversity and ecosystem services is caused by changes in habitats, mainly due to land use change, the spread of invasive species, environmental pollution and climate change. Current unsustainable consumption and production patterns also contribute to the depletion of natural resources and threaten the services provided by ecosystems. At the moment, relatively little is said about ecosystem services, attempts have been made to gather the experience of different countries, but in reality only a few municipalities pay much attention to this issue.